Lobat Pakpak: Kajian Organologi, Ritual, dan Teknik Permainan - Pasaribu, Andika pranata; Fadlin, Fadlin; Ginting, Yoe Anto (Mahesa Research Center, 2025)
This study explores the ritual of making and the playing techniques of the Lobat Pakpak in Sukaramai Village, Kerajaan District, Pakpak Bharat Regency. The background of the research lies in the significance of the Lobat, which functions not only as a musical instrument but also as a medium of spirituality and cultural identity for the Pakpak community. The objectives are to describe the ritual process of crafting the Lobat, explain its playing techniques, and analyze the musical structure of its repertoire. The fieldwork was conducted over a one-week period starting on June 12 until completion, involving six key informants, including instrument makers, traditional players, and cultural leaders. The data were collected through participant observation, in-depth interviews, audio-visual recordings, and musical transcription. A qualitative method with an ethnographic approach was applied. Dhavamony’s theory was employed to examine ritual aspects, Kashima Susumu’s theory for organological study, and Malm and Prier’s theories for musical analysis. The findings reveal that the making of the Lobat combines technical craftsmanship with sacred rituals, while its performance emphasizes breath control, simple fingering, and pentatonic melodic patterns. Thus, the Lobat represents an intangible cultural heritage reflecting spirituality, local wisdom, and the identity of the Pakpak people.